Rethinking Information Systems Projects Using Actor‐Network Theory: A Case of Malawi. Issue 1 (5th December 2017) - Mpazanje, Flora; Sewchurran, Kosheek; Brown, Irwin
Abstract: Organisations invest heavily in Information Systems (IS) projects in the hope of realising business benefits. Yet reports persist of IS projects that all too often fail. Efforts to rescue the situation have so far yielded unsatisfactory results. A number of calls have hence been made to rethink and deepen understanding of IS project management practice. The purpose of this study is to contribute towards this rethink by exploring and describing the as‐lived experiences of stakeholders in IS projects. A case study approach was adopted wherein in‐depth analysis was carried out on an IS project executed in Malawi. Using a developing country such as Malawi as empirical source is novel, as much of the research on IS project management emanates from the developed world. Yet IS project failure is endemic in all contexts. Data was collected and analysed qualitatively using Actor‐Network Theory (ANT) as the lens of enquiry. Key findings were that (1) starting up an IS project is neither simple nor straightforward; it is lengthy and winding; (2) project objectives need not be "cast in stone", as they may be subject to negotiations as key stakeholders are brought in; (3) project success is achieved only when stakeholder interests are strongly interwoven in the project need; (4) involving operational system end users was oddly not seen as critical in the case, and (5) the experience of the project manager will determine the extent to which formal methodologies are rigidly followed in the project. The use of an ANT lens provides for a deeper understanding of IS project processes and outcomes.